Retinopathy of prematurity in India - what can we learn from the polio legacy? - Sam Ebenezer Athikarisamy; Anand Vinekar; Sanjay Patole (Elsevier, 2023)
Summary: Retinopathy of prematurity (ROP) is a vasoproliferative disease of the preterm retina that has the potential to cause vision impairment and blindness. Timely screening and treatment are hence critical for infants at risk for ROP. Screening for ROP is challenging in India owing to the limited resources, a vast at-risk population and lack of awareness among paediatricians and the public. Addressing ROP in India requires a comprehensive approach involving multiple sectors, considering the magnitude of the problem and the expected increase in need for ROP services due to the increased survival of preterm infants following improvements in neonatal care. The success of the Global Polio Eradication Initiative (GPEI) offers valuable lessons for improving ROP services in developing nations by applying its strategies. An approach for primary and secondary prevention of ROP is proposed, and the current challenges and a neonatal-led care model for ROP are discussed.